2006
DOI: 10.2332/allergolint.55.403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of KP-496, a Novel Dual Antagonist for Leukotriene D4 and Thromboxane A2 Receptors, on Contractions Induced by Various Agonists in the Guinea Pig Trachea

Abstract: These results indicate that KP-496 is a selective dual antagonist for LTD(4) and TXA(2) receptors. LTD(4) and TXA(2) play important roles in asthma, and antagonists for these mediators are being used for the treatment of asthma. Thus, KP-496 is expected to become a novel potent therapeutic agent for asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Indeed, these have been shown to be effective when used either alone or in combination for suppressing antigen-induced bronchoconstriction in guinea pigs (Yoshimi et al, 2001). Other drugs have been developed with dual leukotriene D4 and TXA 2 receptor antagonism with efficacy in experimental models of allergic inflammation (Yamada et al, 2003;Ishimura et al, 2006). However, the efficacy of TXA 2 synthase inhibitors and receptor antagonists does not spread to all inflammatory diseases where activated platelets are a component.…”
Section: Antagonists Of Pleiotropic Mediators Released By Plateletsmentioning
confidence: 99%
“…Indeed, these have been shown to be effective when used either alone or in combination for suppressing antigen-induced bronchoconstriction in guinea pigs (Yoshimi et al, 2001). Other drugs have been developed with dual leukotriene D4 and TXA 2 receptor antagonism with efficacy in experimental models of allergic inflammation (Yamada et al, 2003;Ishimura et al, 2006). However, the efficacy of TXA 2 synthase inhibitors and receptor antagonists does not spread to all inflammatory diseases where activated platelets are a component.…”
Section: Antagonists Of Pleiotropic Mediators Released By Plateletsmentioning
confidence: 99%
“…The antagonistic activities of KP-496 for both LTD 4 and TXA 2 are comparable to the cysLT receptor antagonists and TP antagonist already launched [23] . Furthermore, our previous study [24] demonstrated that inhaled KP-496 significantly inhibited antigen-induced bronchoconstriction, while sufficient doses of montelukast and seratrodast did not inhibit it.…”
Section: Introductionmentioning
confidence: 58%
“…KP-496 [2-(N-[4-(4-chlorobenzenesulfonylamino)butyl]-N-[3-(4-isopropylthiazol-2-yl)methoxy]benzyl)sulfamoylbenzoic acid], a novel dual antagonist of cysLT receptor and TP, was synthesized by Kaken Pharmaceutical Co. Ltd. [23,24] and is currently in clinical development as a dry powder inhaler, KP-496DPI. The antagonistic activities of KP-496 for both LTD 4 and TXA 2 are comparable to the cysLT receptor antagonists and TP antagonist already launched [23] .…”
Section: Introductionmentioning
confidence: 99%
“…In the LTD 4 -induced contraction of the trachea, the antagonistic activity of KP-496 was comparable to those of pranlukast and zafirlukast, and was stronger than that of montelukast. Furthermore, the antagonistic activity of KP-496 against the U-46619-induced tracheal contraction was comparable to that of seratrodast [14].…”
Section: Introductionmentioning
confidence: 63%
“…Research indicates that KP-496 is a dual antagonist for LTD 4 and TXA 2 receptors [14]. In an in vitro study using isolated guinea pig trachea, KP-496 produced parallel rightward shifts of both LTD 4 -and U-46619 (a TXA 2 mimetic)-induced contractions in a concentration-dependent manner.…”
Section: Introductionmentioning
confidence: 98%